(untitled) (Damascus University Journal of agriculture sciences, 2026)
The research was conducted at the Abou Jarash Farm, Faculty of Agriculture, Damascus University, during 2020 season, in order to determine the water requirement of cucumber crop of Dutch class (semins) , using tow irrigation methods (drip - surface), With three replicates for each treatment by random sector design, Irrigation process upon the arrival of soil moisture to 80% of field capacity. The results showed the superiority of drip irrigation compared to surface irrigation in the water requirement , which reached ( 3099.5 -5597.7 m3/ha) respectively. Also superiority of drip irrigation compared to surface irrigation with yield increasing and water irrigation saving and water use efficiency, With an increase ratio in yield by(14.6-11.2 ton/ ha) respectively , with an irrigation water saving ratio by (55.4 % ), and increase ratio in water use efficiency by(4.95 -3.04 kg/m3 ) respectively . Also the use of drip irrigation resulted in a increase in dry matter by (5.4-3.3% ) respectively, and in addition to an total sugar by (6.8-4.6 %) respectively, and with vitamin C fruits by (4.4- 3.2 mg /100 g) respectively .